ANALISIS KEBIJAKAN UJIAN NASIONAL TERHADAP EVALUASI AKHIR PENDIDIKAN - Sartina Sartina; Nursiang Nursiang; Faisal Faisal (Institusi Agama Islam Negeri (IAIN) Bone, 2020)
Evaluation is the one of several important activities to increase the quality ofeducation. The national examination is the technique in evaluate education process.Today, debating about pro and contra national examination still in progress. Someexperts, like teacher and politician doubt the effectiveness of national examination,but on the other side many experts believe the national examination is the bestsolution for increasing the quality of education. Despite the weakness especially inpractice, the national examination was good solution for many problem to increasethe quality of education, and in conceptual’s context the national examination wasthe effective way for increasing quality. Besides that, the national examination wasa mandate from constitution (UU No. 20/2003 and PP No. 19/2005). So, it isunfair if national examination must be cancelled only based on several doubt from some expert without give chance to government for reduction the weakness.